Factors affecting the success of NGO interventions in social service provision for the rural poor communities in Zimbabwe: case of Luunga Ward 1 in Binga District - Mutale, Quegas (Midlands State University, 2017)
This research was built upon the thrust to assess the factors affecting the success of NGO interventions in social service provision for the rural poor communities in Zimbabwe, citing the case of Luunga ward 1 in Binga. The objectives that drove this research were: to identify the types of social services being offered by NGOs to the community of Luunga Ward 1 in Binga District; to identify the strategies used by NGOs in the provision of social services to the community of Luunga Ward 1 in Binga District; to examine the factors that affect NGO interventions in the provision of social services to the community of Luunga Ward 1 in Binga District; and to establish how NGO social services programming in Luunga ward 1 in Binga assists in meeting the rural poor‟s basic social needs. The concepts NGO, social service, rural poor and communities in line with how they were contextualised in the study were reviewed. Global, African and national overview was synthesised to indicate that NGOs‟ presence is noted at every level in the world intervening in diverse aspects of human lives. As a human development focus, NGO social service delivery efforts were examined in the literature basing on the research objectives so as to create rapport between theory in literature and the empirical findings. A mixed research methodology was applied for this research. Both qualitative and quantitative research designs were adopted in this study. To enhance the validity and reliability, both probability and non-probability sampling techniques were employed. 40 respondents were sampled out of a target population of 236, and these involved 20 community members, 6 government officials, 4 NGO representatives, 6 ward level local leaders and 4 extension workers. Research instruments used were questionnaires, interviews with both open-ended and closed ended questions, and also observation. Empirical evidence from this research revealed that nature of Zimbabwean politics, lack of adequate funding, socio-cultural and religious issues, the legal framework, environmental factors, poor roads and communication infrastructure, community attitudes, poor monitoring and evaluation, lack of meaningful community participation, engagement and involvement, lack of ward development plan, poor coordination and the knowledge gap among others contributed significantly to the failure of NGO interventions in social service provision in Luunga ward in Binga. It was however discovered that despite the NGO efforts, the rural poor in Zimbabwe are still subjected to lack of adequate social services. The research concluded that the government, NGOs, donor organisations and communities all played a significant role in the level of success of NGO interventions in social service delivery in Luunga ward, Binga. There had been failure of adequate coordination among the partners in development. Therefore, recommendations were passed in the research that the government need to create an enabling environment for NGOs to successfully deliver social services, and also empower locals not to just wait for NGO assistance but also strive to make ends meet. NGOs need to intensify needs assessments, donor organisations need to consider that their conditions should be pro-poor, and that communities should work hand-in hand with all development partners. Therefore, the interventions need to be stakeholder wide and inclusive.